Communication Opportunities for Elementary School Students who use Augmentative and Alternative Communication. (1st October 2016) - Andzik, Natalie R.; Chung, Yun-Ching; Kranak, Michael P.
Abstract: Augmentative and alternative communication (AAC) systems serve as the primary communication mode for many students with complex communication needs. The aim of this study was to describe the naturally occurring communication opportunities of students using AAC systems. We observed 23 students for a total of 117 hours across general education, special education, and non-academic settings. For each communication event, we recorded the setting, communication partner, student communication mode, availability of the AAC system, independent or prompted responses, and the consequence. Communication events primarily occurred with adults and very few spontaneous initiations were observed. On average, students were presented with 17 opportunities to respond per hour. However, in nearly half of these opportunities, students did not have access to their AAC system. Results from our observations indicated more deliberate efforts are needed to ensure students have appropriate access and opportunity to use AAC systems across school environments.